The Effect Of Use Of Electronic Card (Edu Smart Amanah) on Modern Retail, Consumptive Behavior of Students, Students of Modern Salaf Islamic Boarding School Thohir Yasin - Delah, Laila Himni; Rizqiwati, Baiq Yuliana; Aini, Qurratul (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
This research aims To find out the effect of the use of electronic cards on modern retail, the consumptive behavior of students, students of the at Thoir Yasin's Modern Salaf Islamic Boarding School. Partially and simultaneously. The method used is a quantitative method. The study subjects were 61 people. The data collection techniques and instruments used were pe questionnaire , and interviews. The data from this study were tested using the classical assumption test, multiple linear regression t test  and f test  . The results of the study show: 1) partially the variable use of electronic cards (X1) towards modern retail (Y1), the results of the t count are 3.368 > T table 2.001. So it can be assumed that there is a partial influence of the electronic card variable X1 on Y1 of modern retail. 2) partially the variable use of electronic cards (X1) on consumptive behavior (Y2), the value of t count is 4.726 > T table is 2.001. So it can be said that there is a partial influence of the electronic card variable (X1) on consumer behavior (Y2). 3) Simultaneous use of electronic cards (X1) on modern retail (Y1), consumptive behavior (Y2), calculated F value of 6.072 > F table 3.15. So it can be concluded that there is a simultaneous (together) effect of the X1 electronic card variable on modern retail (Y1), consumptive behavior (Y2) of Islamic students, students of the takmili class at the modern salaf Islamic boarding school thohir yasin lendang jackfruit.